Universal capillary screening for chronic autoimmune, metabolic and cardiovascular diseases: feasibility and acceptability of the UNISCREEN study - Angiulli, Sara; Merolla, Aurora; Borgonovo, Elisa; De Lorenzo, Rebecca; Spadoni, Serena; Fontana, Barbara; Manganaro, Giuseppina; Rela, Elena; Bongiovanni, Alberto; Peracino, Rita; Bellino, Chiara; Pata, Giulia; et al. (Frontiers in Public Health, 2025)
BackgroundUNISCREEN is a general population study aiming at evaluating feasibility and acceptability of universal screening for chronic autoimmune (type 1 diabetes and celiac disease) and metabolic/cardiovascular diseases (dysglycemia, type 2 diabetes, dyslipidemia, hypertension) across all age groups using capillary blood sampling by fingerprick to measure disease risk markers.MethodsUNISCREEN was conducted in the Cantalupo fraction, Cerro Maggiore, Milan, Italy, counting 3,061 inhabitants between 1 and 100 years of age. Participation was voluntary, following a public call. Participants were invited to respond to feasibility and acceptability questionnaires immediately before and after the screening procedures, which included the following: capillary blood drawing for immediate measurement of metabolic parameters (glucose, glycated hemoglobin, total-, HDL- and calculated LDL-cholesterol, triglycerides) and late autoantibody assays; blood pressure measurement; brief consultation with a physician providing feed-back on immediate results and health recommendations. The study was registered as ClinicalTrials.gov NCT05841719.ResultsThe study included 1,535 participants (50.1% of local population). A single fingerprick was sufficient for all measurements in 47.1% of cases, while up to two were necessary in 86.9% of cases. Complete glucose and lipid panels were obtained in 1382 participants (90.0%). Sufficient serum for late autoantibody testing was obtained in 99.7% of participants. The questionnaires showed overall satisfaction, with over 90% of participants considering capillary sampling simple and practical, and preferring it to venous sampling. Before screening, 24.0% adults and 31.7% children’s parents were worried about the possibility of being diagnosed or identified as being at risk; worries decreased to 21.3 and 23.4%, respectively, after medical consultation. The immediacy of some result communication possibly contributed to reducing the anticipatory anxiety.ConclusionThe UNISCREEN study shows that universal screening for chronic autoimmune, metabolic and cardiovascular diseases in the general population using capillary blood testing is feasible and acceptable.